The turbulent life of the Working Time Directive. Issue 1 (February 2018) - Nowak, Tobias
The case of the Working Time Directive (WTD) is a prime example of a failed attempt by the Member States and the Commission to counter rulings of the European Court of Justice (CJEU) by legislative overrule. Outsourcing the decision making process to the social partners also did not deliver the desired results. After years of trying to reform the WTD, the Commission changed its strategy and issued an interpretive communication instead. However, it is doubtful that this communication will solve all that is wrong with the WTD. What were the obstacles to legislative overrule in this case? What other strategies in avoiding the consequences of CJEU rulings do the Member States apply? What will the future of WTD look like?